Interleukin-22 is elevated in the atrium and plasma of patients with atrial fibrillation and increases collagen synthesis in transforming growth factor-β1-treated cardiac fibroblasts via the JNK pathway - Wu, Yongxin (Exp Ther Med, 2020)
Our previous studies demonstrated that interleukin (IL)-22 is involved in cardiovascular diseases such as hypertension, cardiac fibrosis and aortic dissection. The purpose of the present study was to detect IL-22 expression in patients with atrial fibrillation (AF). Atrial tissue was collected from donors with sinus rhythm and patients with permanent AF, and the expression level of IL-22 and its receptors (IL-22R1 and IL-10R2) in both the left atrium (LA) and right atrium (RA) of each sample was detected. Blood samples were also obtained from donors with paroxysmal, persistent and permanent AF and from donors without AF history, and IL-22 levels were measured. In addition, the effects of IL-22 on collagen synthesis in TGF-β1-treated cardiac fibroblasts were investigated. IL-22R1, IL-10R2 and IL-22 expression was elevated in both the LA and RA in permanent AF patients. Elevated IL-22 expression positively correlated with the collagen areas and fibrosis marker levels in the atria of these patients. Plasma IL-22 levels were higher in AF patients compared with healthy donors and increased with increasing AF duration (from paroxysmal to persistent to permanent AF). A positive correlation was observed between IL-22 levels and TGF-β1 levels in AF patients. In vitro, recombinant mouse IL-22 treatment upregulated α-SMA, collagen I and collagen III expression in TGF-β1-treated cardiac fibroblasts. These effects were reversed by SP600125, an inhibitor of the JNK pathway. To conclude, IL-22 levels are elevated in patients with AF and may exacerbate collagen synthesis in TGF-β1-induced cardiac fibroblasts. IL-22 may also influence AF by activating the JNK pathway.